Advanced Anaerobic Digestion and Associated Process for Zero Discharge Biowastes Treatment - Manilal, V B; Chitrajit, B; Nath, R S Dipin (International Journal of Environment, Agriculture and Biotechnology, 2019)
Anaerobic digestion is an attractive option for the treatment of organic wastes because of the net energy gain from the process to offset part of the operational cost. Invariably management of discharges from the anaerobic digester requires further processing and most of the known methods are either expensive or complex to practice. A complete solution to the problem of biowastes treatment is discussed in this paper through an improved anaerobic digestion process where no additional water is to be used in the operation, and the conversion of the digestate to solid manure. The tubular anaerobic digester employed in the study could remove nearly 90% of the volatile solids and produce biogas of around 550 litres/kg VS loading. The management of digester discharge was studied by following a method of evapouration drying by mixing with pre-dried discharged digester slurry to maintain combined moisture level below 60%. The average evapouration rate of moisture by this method was 211.6 ±16.6 g/kgTS/day under ambient conditions.